SEARCHES OF HISTORICAL SOURCES – PRIMARY PRINCIPLE OF MAGDALENA KARČIAUSKIENĖ PEDAGOGY - Valatkienė, Stasė (Acta Paedagogica Vilnensia, 2009)
The purpose of this article was to disclose the views of professor Magdalena Karčiauskienė as well as evaluation of her pedagogical phenomenon from the historical comparative point of view. The scientist’s conception of searches of historical sources is presented and the importance of historical continuity principle for modern Lithuanian school and pedagogical science is grounded. The professor M. Karčiauskienė’s scientific pedagogic research is related not only with the development of Lithuanian system of education but also with the trends of the world school and the development of pedagogical thought. With a deep insight into classical pedagogy and new pedagogical trends of the 20th century the researcher does not counterpoise them, but expresses her opinion against their extremities, accentuating the importance of their synthesis. Each pedagogical issue is investigated from the historical perspective, revealing their essence, historical origin, highlighting the importance of the principle of historical continuity for the contemporary school and the science of education.